Secoyanhusamine A, an Oxidatively Ring-Opened Isoquinoline Inner Salt From Corydalis yanhusuo - Wang, Lingyan; Xia, Huan; Wu, Yuzhuo; Wang, Yanan; Lin, Pengcheng; Lin, Sheng (Frontiers in Chemistry, 2022)
Secoyanhusamine A (1), a rare rearranged seco-isoquinoline alkaloid derived from ring oxidative cleavage, was isolated from an aqueous extract of Corydalis yanhusuo tubers, together with its biosynthetic precursor dehydrocorybulbine (2). Secoyanhusamine A (1) was the first example of a highly oxidized isoquinoline inner salt resulting in a 5-(2-azanylethyl)-2-carboxylate-4-oxo-4H-pyran ring system. The biosynthetic pathway of 1 was also postulated. Secoyanhusamine A (1) exhibited potent inhibition against acetylcholinesterase (AChE) with an IC50 value of 0.81 ± 0.13 μM. Molecular simulation docking demonstrated that 1 created a strong interaction with Asp-74 residue of AChE via attractive charge of the quaternary nitrogen.